2017
DOI: 10.1038/s41598-017-13864-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical Controlled Terahertz Modulator Based on Tungsten Disulfide Nanosheet

Abstract: The terahertz (THz) modulator, which will be applied in next-generation wireless communication, is a key device in a THz communication system. Current THz modulators based on traditional semiconductors and metamaterials have limited modulation depth or modulation range. Therefore, a THz modulator based on annealed tungsten disulfide (WS2, p-type) and high-resistivity silicon (n-type) is demonstrated. Pumped by a laser, the modulator presents a laser power-dependent modulation effect. Ranging from 0.25 to 2 THz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…While many different approaches and devices for THz modulation have been demonstrated in existing literature, our approach offers a unique combination of characteristics. Modulation with superior bandwidth can be achieved with uniform heterostructures and films, but it is challenging to achieve low insertion loss and large modulation depths . Such large modulation depths can be achieved with tunable resonant structures, but the effect is typically not broadband .…”
Section: Resultsmentioning
confidence: 99%
“…While many different approaches and devices for THz modulation have been demonstrated in existing literature, our approach offers a unique combination of characteristics. Modulation with superior bandwidth can be achieved with uniform heterostructures and films, but it is challenging to achieve low insertion loss and large modulation depths . Such large modulation depths can be achieved with tunable resonant structures, but the effect is typically not broadband .…”
Section: Resultsmentioning
confidence: 99%
“…Common pump beams with wavelengths of 808 and 532 nm [18,[31][32][33][34], respectively, and silicon resistivity of 1000 Ω•cm were employed to simulate the THz modulation with different nanostructures. As is known, longer wavelengths have a stronger ability to penetrate silicon.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…As seen in Figure 8a, the presence of MoS 2 on Si enhances the attenuation of the terahertz waves as compared to bare silicon under the same pumping power. Additionally, Fan et al [125] demonstrated a WS 2 -Si hybrid device, which operates as a broadband terahertz modulator. Carrier diffusion into MoS 2 from Si results in the enhancement of terahertz modulation in this heterostructure.…”
Section: Mos 2 -Si Hybrid For Terahertz Modulationmentioning
confidence: 99%